The pdfTeX user manual - Thánh, H; Rahtz, S (TeX Users Group, 1997)
The pdfTeX project started in 1996 at the Faculty of Informatics, Masaryk University, Brno, Czech Republic. It forms a primary part of the MSc and PhD research of Han The Thanh, under the supervision of Jiří Zlatuška and Petr Sojka. The main purpose of the project was to create an extension of TeX that could create PDF directly from TeX and improve/enhance the result of TeX typesetting with the help of PDF. pdfTeX contains TeX as a subset. When PDF output is not set, it produces normal DVI output; when PDF output is selected, pdfTeX produces PDF output that looks identical to the DVI output. The next stage of the project, apart from fixing any errors in the program, is to investigate alternative justification algorithms, possibly making use of multiple master fonts. pdfTeX is based on the original TeX sources and web2c, and has been successfully compiled on Unix, Amiga, Win32 and DOS systems. It is still under beta development and all features are liable to change. This manual was compiled by Sebastian Rahtz from notes and examples by Han The Thanh. Many thanks are due to members of the pdfTeX mailing list (most notably Hans Hagen), whose questions and answers have contributed much to this manual.